Antibacterial Activities Test of Acne Gel Mask Black Cumin Oil (Nigella sativa Linn) combined with Olive Oil (Olea europaea var. Europea) - Lestari, Uce; Muhaimin, Muhaimin; Yuliana, Yuliana; Mekeama, Luri (Indonesian Journal of Biological Pharmacy, 2024)
Sebaceous glands produce excessive oil causing clogged pores and inflammation. The inflammation produces lesions called acne. Plants that have natural antibacterial activity are black cumin (Nigella sativa Linn) and olive (Olea europaea var. Europea) which contain bioactive compounds. The combination of these two natural ingredients in the form of a gel mask makes it easy to apply as an acne medicine. The study aims to determine the inhibitory activity of black cumin and olive oil gel masks (MJHZ) against propionibacterium acne, staphylococcus aureus and staphylococcus epidermidis bacteria. The sample was distilled into essential oils. Inhibitory activity against bacteria using the disk diffusion method. The results of the MIC analysis of bacteria from MJHZ have bacteriostatic activity against P.acne, S.aureus and S.epidermidis bacteria at a concentration of 0.039%. After being formulated into a gel mask, MJHZ showed that the lower the concentration of the two oils, the greater the inhibitory power against P. acne, S. aureus and S. epidermidis bacteria. This shows that the MJHZ gel mask with a concentration of 0.5% each has the greatest inhibitory activity against P. acne bacteria of 21.55 mm compared to the inhibitory power against other bacteria such as S. aureus and S. epidermidis. Therefore, the MJHZ gel mask has the potential as an acne medication.Keywords:  antiacne, black cumin, olive, propionibacterium acne